Character Design of Pencak Silat Figures Based on Martial Arts Culture and Values in Fighting Games - Adita Octaviani; Sintia Catur Sutantri (Advanced Qualitative Research, 2025)
Indonesia has the martial art of Pencak Silat, where Silat Warriors have a distinctive character. This study was motivated by the lack of Pencak Silat values that are implemented and visualized in the character design of fighting games. It is feared that this will make Pencak Silat as an Indonesian martial art even more extinct because it has to compete with other foreign martial arts. The purpose of this research is to contribute, reference, and direct the development of digital products with the theme of Pencak Silat to prioritize original cultural values in fighting games. This research uses a qualitative methodology. Data collection through interviews, field observation, and literature review from relevant sources. The data obtained was analyzed using theories about Pencak Silat and the basic movements of Pencak Silat and Edugame. Until now, no research has been conducted on the inclusion of Pencak Silat values in fighting-themed games. Therefore, the results of the research that focuses on PERSINAS ASAD and PERISAI DIRI as a Pencak Silat group have an impact on determining future fighting game flow and as an educational realm that is typical of Indonesian Pencak Silat culture. Pencak Silat is rarely found in digital entertainment, especially in video games. Thus, the group’s goal is to improve human quality so that it can preserve the culture of Indonesia